Respuesta :

Answer:

Step-by-step explanation:

g(2) = 3(2) + 1 = 6 + 1 = 7

h(7) = 2(7) - 1 = 14 - 1 = 13

Using composite functions, it is found that:

[tex](h \circ g)(2) = 13[/tex]

The composition of functions h(x) and g(x) is given by:

[tex](h \circ g)(x) = h(g(x))[/tex]

In this problem, the functions are:

[tex]h(x) = 2x - 1[/tex]

[tex]g(x) = 3x + 1[/tex]

Then:

[tex]h(g(x)) = h(3x + 1) = 2(3x + 1) - 1 = 6x + 2 - 1 = 6x + 1[/tex]

At x = 2:

[tex](h \circ g)(2) = 6(2) + 1 = 13[/tex]

A similar problem is given at https://brainly.com/question/23458455

ACCESS MORE